Diseño e implementación de un dispositivo de estimulación no invasiva para tratamiento de APNEA obstructiva del sueño (2017)
The present graduation project presents the development of a device that manages to detect the phases of the breathing of a person, in order to generate a transcutaneous stimulation with a wave of 50Hz, with the aim of implementing a non-invasive system for the treatment of obstructive sleep apnea. This device has a set of sensors to facilitate the detection process, plus a pair of electrodes which should be located near the hypoglossal nerve. The main objective of the project is to model the electronic design for a noninvasive stimulation device for the treatment of obstructive sleep apnea and to validate the functioning of the same. In addition, it seeks to fulfill the following purposes: reduce the error that can occur in the intake of data, design a low-consumption device with the objective of implementing a portable version of the same, determine the protective elements that allow a high safety...